Sustainable urban transport policy in emerging countries – case study of Mexico City - Paradowska, Monika (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
Negative external effects of transport are a huge problem of contemporary cities, because of adverse effects on socio-economic development. These processes are visible not only in high or medium developed countries, but also in high populated, big metropolises in so called emerging countries, such as China, India, Brazil or Mexico. This paper is aimed at presenting the selected aspects of sustainable urban transport policy in the capital of one of these countries – Mexico – as well as at describing the specificity of creating instruments for sustainable transport resulting from various conditions. There are different sources used in the paper regarding sustainable transport in Mexico, including reports and statistical data of the World Bank.